The CoREST/REST Repressor Is both Necessary and Inimical for Expression of Herpes Simplex Virus Genes - Guoying Zhou (American Society for Microbiology, 2011)
ABSTRACT Herpes simplex virus type 1 encodes three sets of genes, α, β, and γ, whose expression is sequentially ordered in a cascade fashion. The transactivators of α genes comprise virion protein 16 (VP16) and the cellular proteins octamer binding protein 1 (Oct1) and host factor 1 (HCF1). Efficient transition from α to β gene expression requires the α protein ICP0 (infected cell protein 0). Earlier studies have shown that this protein binds to CoREST and displaces HDAC1 from the CoREST/REST/lysine-specific demethylase 1 (LSD1) repressor complex. Ultimately, the components of the repressor complex are translocated at least in part into the cytoplasm. A key event in activation of α genes is the recruitment of LSD1 to demethylate histones bound to the α gene promoters. LSD1 is unstable in the absence of its partner, CoREST, and raises the question of whether both CoREST and REST are involved in the initiation of transcription of the α genes. Here we show that CoREST or REST small interfering RNAs (siRNAs) destabilize CoREST, REST, LSD1, and Sin3A, another component of the repressor complex. In cells transfected with REST or CoREST siRNA, the accumulation of α proteins and mRNAs is delayed in comparison to those of mock-transfected or control siRNA-transfected cells. The LSD1/CoREST/REST compressor complex is thus sequentially necessary and subsequently inimical for viral gene expression. IMPORTANCE Herpes simplex virus type 1 (HSV-1) is globally regulated at the following four checkpoints: (i) the activation of α (immediate-early) genes, (ii) the point of transition from α to β and γ gene expression, (iii) the silencing of viral genes for the establishment of the latent state, and (iv) the reactivation of viral genes on termination of latency. Earlier studies showed that the transition from α to β and γ gene expression involves the suppression of the HDAC1/lysine-specific demethylase 1 (LSD1)/CoREST/REST (HLCR) repressor complex. More recently, this laboratory reported evidence suggesting that in sensory neurons, HSV-1 hijacks the HLCR complex to silence itself for the establishment of latency. This report extends the observation that LSD1 is required for expression of the α genes to show that the HLCR complex is involved in this process. Thus, HSV-1 has evolved an intimate relationship with the HCLR complex to regulate its gene expression and, by extension, its fundamental interactions with its human host.